Karakteristik mutu karbohidrat dan evaluasi mutu sensoris minuman fungsional berbasis FOS dan inulin - Danu Indra Wardhana; Ara Nugrahayu Nalawati; Andika Putra Setiawan; Shinta Artamevia Ramadhani; Oppy Valencia (Fakultas Pertanian Universitas Yudharta Pasuruan, 2023)
Introduction: Fructooligosaccharides (FOS) and inulin are some of the many bioactive elements that are often used in functional food products. FOS and inulin compounds have various benefits that can be used as low-calorie food products and as raw materials for making fructose syrup. So that FOS and inulin compounds have the potential to be developed into functional drinks. The purpose of this study was to evaluate the quality characteristics of carbohydrates in functional drinks FOS and inulin, as well as to determine the level of preference or feasibility of a product so that it can be accepted by panelists (consumers). Method: The research was conducted in two stages. The first stage was the preliminary stage which includes the production of FOS with PDA solid media, extraction of inulin from dahlia tubers, and the formulation of FOS and inulin functional drinks. The second stage was the main research by conducting chemical quality characteristics in the form of reducing sugar content, fructose, sucrose, glucose, inulin, soluble fiber, and organoleptic tests. Results: Based on the observations, several characteristics of the carbohydrate quality of functional drinks based on FOS and inulin were obtained, namely reducing sugar levels ranging from 0.22 to 5.60%. Fructose and sucrose levels of functional drinks based on FOS and inulin ranged from 1-2%, while glucose levels were between 0.1-2%. The levels of inulin and soluble fiber in functional drinks based on FOS and inulin were 55-86% and 2-5%, respectively. Also, the pH value of functional drinks based on FOS and inulin ranged from 5-7. Conclusion: The results of the organoleptic test showed that the best functional drink based on FOS and inulin was in the AD treatment, namely the addition of 7 grams of inulin and 50 ml of fructooligosaccharides.